2018
DOI: 10.1016/j.jbiomech.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography can assess the in-vivo nonlinear mechanical behavior of heel-pad

Abstract: This study combines non-invasive mechanical testing with finite element (FE) modelling to assess for the first time the reliability of shear wave (SW) elastography for the quantitative assessment of the in-vivo nonlinear mechanical behavior of heel-pad. The heel-pads of five volunteers were compressed using a custom-made ultrasound indentation device. Tissue deformation was assessed from B-mode ultrasound and force was measured using a load cell to calculate the force - deformation graph of the indentation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…In a study about spatial dependent mechanical properties of the heel pad using SWE, Young's modulus was not used considering the heterogeneity of the tissue (Lin et al, 2017). Thus, SWE should be used to assess the changes in stiffness of the tissue but not to quantify stiffness itself (Chatzistergos et al, 2018).…”
Section: Feasibility and Reproducibility Of 2d Swe In Canine Soft Tismentioning
confidence: 99%
“…In a study about spatial dependent mechanical properties of the heel pad using SWE, Young's modulus was not used considering the heterogeneity of the tissue (Lin et al, 2017). Thus, SWE should be used to assess the changes in stiffness of the tissue but not to quantify stiffness itself (Chatzistergos et al, 2018).…”
Section: Feasibility and Reproducibility Of 2d Swe In Canine Soft Tismentioning
confidence: 99%
“…Localised stiffening was assessed by measuring changes in the distribution of SW propagation speed in an axial imaging plane at the centre of the heel (Figure 1a). Previous research from the authors of this study had shown that increased or decreased SW speed in the plantar soft tissue is a reliable indicator for tissue stiffening or softening respectively 4 . To precondition the plantar soft tissue and eliminate the effect of loading history, the participants were asked to walk barefoot the length of the lab twice before imaging (≈80 steps).…”
Section: Resultsmentioning
confidence: 73%
“…In this study, changes in tissue biomechanics were assessed in 5mm wide circular areas close to the skin surface (Figure 1c-e). The effect of overloading in deeper tissues was not assessed because SW elastography cannot produce reliable measurements close to bony surfaces 4,5 . The use of alternative elastography techniques could enable the investigation of the effect of overloading on different plantar soft tissue layers 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear behaviour of tissue causes errors in the measurements made since, in most clinical settings, the pressure from ultrasound probes is unregulated. This phenomenon, known as “tissue stiffening” or “strain stiffening”, is present in most soft tissues, for example, breast tissue [ 11 ], heel pad [ 12 , 13 ], calf muscle [ 14 ] and thyroid gland [ 15 ]. The occurrence of tissue stiffening is especially detrimental for cervical elastography as the probe is in direct contact with the tissue, and the shape of the probe causes non-uniform deformation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%